All that remains : a renowned forensic scientist on death, mortality, and solving crimes - Black, Sue M. (Arcade Publishing, 2019)
Black has lived her life eye to eye with the Grim Reaper, and she writes vividly about it in this book, which is part primer on the basics of identifying human remains, part frank memoir, and part no-nonsense but deeply humane introduction to the reality of death in our lives. She recounts her first dissection; the mortal remains in her lab and at burial sites as well as scenes of violence, murder, and criminal dismemberment; and about investigating mass fatalities due to war, accident, or natural disaster. In doing so, she reveals how forensic science has developed-- and what her work has taught her about human nature. -- adapted from jacket